A Systematic Review of Bilateral Upper Limb Training Devices for Poststroke Rehabilitation. (23rd October 2012) - van Delden, A. (Lex) E. Q.; Peper, C. (Lieke) E.; Kwakkel, Gert; Beek, Peter J.
Abstract : Introduction . In stroke rehabilitation, bilateral upper limb training is gaining ground. As a result, a growing number of mechanical and robotic bilateral upper limb training devices have been proposed. Objective . To provide an overview and qualitative evaluation of the clinical applicability of bilateral upper limb training devices. Methods . Potentially relevant literature was searched in the PubMed, Web of Science, and Google Scholar databases from 1990 onwards. Devices were categorized as mechanical or robotic (according to the PubMed MeSH term of robotics). Results . In total, 6 mechanical and 14 robotic bilateral upper limb training devices were evaluated in terms of mechanical and electromechanical characteristics, supported movement patterns, targeted part and active involvement of the upper limb, training protocols, outcomes of clinical trials, and commercial availability. Conclusion . Initial clinical results are not yet of such caliber that the devices in question and the concepts on which they are based are firmly established. However, the clinical outcomes do not rule out the possibility that the concept of bilateral training and the accompanied devices may provide a useful extension of currently available forms of therapy. To actually demonstrate their (surplus) value, more research with adequate experimental, dose-matched designs, and sufficient statistical power are required.